At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
It looks like we're given
z₁ = 1 - (2 - √3) i
z₂ = -2 - 2i
and we want to find
(i z₁ z₂)²
z₁ lies in the fourth quadrant of the complex plane, so
|z₁| = √(1² + (-2 + √3)²) = 2√(2 - √3)
arg(z₁) = arctan(-2 + √3)
while z₂ lies in the third quadrant, so
|z₂| = √((-2)² + (-2)²) = 2√2
arg(z₂) = arctan(-2 / -2) - π = arctan(1) - π = -3π/4
so their polar forms are
z₁ = 2√(2 - √3) exp(i arctan(-2 + √3))
z₂ = 2√2 exp(-i 3π/4)
Before we continue, we can actually simplify the argument to z₁. Let θ = arg(z₁). From its polar form, it's evident that
2√(2 - √3) cos(θ) = 1
which reduces to
cos(θ) = 1 / (2√(2 - √3))
Recall the half-angle identity,
cos²(x) = (1 + cos(2x))/2
By taking squares on both sides, we have
cos²(θ) = 1 / (8 - 4√3)
(1 + cos(2θ))/2 = 1 / (8 - 4√3)
1 + cos(2θ) = 1 / (4 - 2√3)
cos(2θ) = (-3 + 2√3) / (4 - 2√3)
cos(2θ) = √3/2
2θ = arccos(√3/2) + 2nπ or 2θ = -arccos(√3/2) + 2nπ
(where n is any integer)
2θ = π/6 + 2nπ or 2θ = -π/6 + 2nπ
θ = π/12 + nπ or θ = -π/12 + nπ
We know that z₁ lies in the fourth quadrant, so θ = -π/12.
All this to say
z₁ = 2√(2 - √3) exp(-i π/12)
z₂ = 2√2 exp(-i 3π/4)
Since i = exp(i π/2), we then have
i z₁ z₂ = 4 √(4 - 2√3) exp(i (π/2 - π/12 - 3π/4))
… = 4 √(4 - 2√3) exp(-i π/3)
and squaring both sides gives
(i z₁ z₂)² = 16 (4 - 2√3) exp(-i 2π/3)
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.